Association of Diabetic Retinopathy with Angiographic Severity of Coronary Artery Disease in Patients with Non-ST Elevation Myocardial Infarction (Cardiovascular Journal, 2022)
Background: Bed side ophthalmoscopic examination is a simple measure of diagnosis of diabetic retinopathy and has been shown to be a predictor of poor outcome in various cardiovascular conditions including coronary artery disease. The present study was intended to find the relationship between diabetic retinopathy with the severity of coronary artery disease in patients with non ST elevation myocardial infarction (NSTEMI).Methods: This cross-sectional observational study was conducted with a total of 120 NSTEMI patients with diabetes undergoing coronary angiogram and also fundoscopic examination with fundal photography during the index hospitalization. Study subjects were divided into two groups on the basis of diabetic retinopathy (Group-I: NSTEMI with diabetic retinopathy; Group- II: NSTEMI without diabetic retinopathy). Severity of coronary artery disease was determined by Gensini score and correlation between diabetic retinopathy and Gensini score was assessed.Results: Gensini score was significantly higher in patients with diabetic retinopathy than that in patients without diabetic retinopathy (62.2±27.7 vs. 43.3±25.3, p